2023
DOI: 10.1021/acscatal.2c04978
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trifluoromethyl-Substituted Allenols via Catalytic Trifluoromethylbenzoxylation of 1,3-Enynes

Abstract: Allenol has been identified as a versatile building block for organic synthesis, and numerous efforts have been made to synthesize and apply allenol. However, limited efforts have been made to obtain a trifluoromethyl-substituted allenol. Here, by using a readily available 1,3-enyne as the starting material, a coppercatalyzed trifluoromethylbenzoxylation process was developed for efficient synthesis of trifluoromethyl-substituted allenols using Togni-II reagent as the reaction partner. Triple roles of the Togn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 91 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…This selectivity is dependent on the enone substrate, but the NCS isomer could be easily purified by column chromatography. This reactivity represents one of the few examples where TMSNCS is reported as a reagent for the formation of isothiocyanates (-NCS), [40][41][42][43][44] while there are many examples of its use to form thiocyanates (-SCN). [45][46][47] First, we checked the electronic effects of the aromatic substituents and found that enones with electron-donating (Me, OMe) and electron-withdrawing (CN, F, CF 3 , NO 2 ) groups at the para position of the phenyl ring were well-tolerated, giving the desired isothiocyanato products (2b-2g) in excellent yields (87-94%).…”
Section: Resultsmentioning
confidence: 99%
“…This selectivity is dependent on the enone substrate, but the NCS isomer could be easily purified by column chromatography. This reactivity represents one of the few examples where TMSNCS is reported as a reagent for the formation of isothiocyanates (-NCS), [40][41][42][43][44] while there are many examples of its use to form thiocyanates (-SCN). [45][46][47] First, we checked the electronic effects of the aromatic substituents and found that enones with electron-donating (Me, OMe) and electron-withdrawing (CN, F, CF 3 , NO 2 ) groups at the para position of the phenyl ring were well-tolerated, giving the desired isothiocyanato products (2b-2g) in excellent yields (87-94%).…”
Section: Resultsmentioning
confidence: 99%
“…Using Togni-II reagent, Yang and Cao developed an efficient method for the copper-catalyzed radical trifluoromethylbenzoxylation of 1,3-enyne derivatives ( 111 ) for preparing CF 3 -substituted allenols ( 112 ). (Scheme d) . Notably, mechanistic studies also provide some evidence suggesting that in this reaction, Togni-II reagent plays three roles: the oxidant, the CF 3 -radical source, and the oxygen-functionality sources.…”
Section: Radical-addition-based C–o Bond Formationmentioning
confidence: 92%
“…(Scheme 7d). 82 Notably, mechanistic studies also provide some evidence suggesting that in this reaction, Togni-II reagent plays three roles: the oxidant, the CF 3 -radical source, and the oxygen-functionality sources. of 1,3-enynes with different substituted alkene moieties to produce valuable trifluoromethyl-substituted allenolates in good yield.…”
Section: O-nucleophile-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yang and Cao group, in 2023, reported a Cu-catalyzed ATRA reaction of 1,3-enynes with Togni II reagent for making trifluoromethylbenzoxylated allenes 24 ( Scheme 24 ) [ 56 ]. The Togni II reagent plays triple roles in the reaction process, including the source of CF 3 radical, the nucleophile for the second functionalization, and an oxidant for Cu catalysis.…”
Section: 14-difunctionalization Reactionsmentioning
confidence: 99%